An interplay between formal and informal development:A case study of two neighborhoods in the Tenth of Ramadan City - Mansour, Mennat Allah Mohamed Awad (AUC Knowledge Fountain, 2020)
The over-congestion of the Nile valley and Delta region led to the political conclusion that new desert cities were necessary to attract the ever-growing population and reduce the pressure on existing Nile Valley cities. The new desert cities that were meant to house a total population of 12 million people, today, four decades after the initiative started, only house a fraction of this target population, failing to attract residents in spite of the countless housing units left vacant. It is important to study the underlying factors that led to this urban problem and population gap to inform the planning process of future cities. In an urban context like Egypt’s with two thirds of its urban population residing in informal settlements, it becomes necessary to acknowledge this reality and to study extensively the phenomenon of informality, especially in planning practices to see how it may inform the rise of more integrative and sustainable built environments. This research aims to shed light on the interplay between the formal and informal development processes and how (if it all) it can create alternative sustainable urban growth models. Through a qualitative phenomenological research approach, two neighborhoods are studied in depth to reach a profound comprehension of their ‘reality’, in the Tenth of Ramadan City, which was the first new city to be established. Megawra 14, which contains the only Core Housing Scheme in the Tenth of Ramadan City and can be considered a case of interplay between formal and informal development, and Megawra 13, which contains governmental public housing apartment buildings and considered a formally planned neighborhood. Followed by a sustainability analysis, which shed light on how sustainable the opposite planning strategies of the two neighborhoods are, under the three dimensions of social, physical and economic sustainability. The three dimensions were further subcategorized into emergent themes, such as, sense of ownership, safety, density, utilization of space and accessibility to services, reflecting on each neighborhood’s degree of sustainability for each theme. The analysis conveys the strengths and weakness of both contrasting neighborhoods in terms of their sustainability. Finally arriving to the conclusion that the many new Egyptian cities in their planning stages can benefit a lot by integrating informal development patterns in their formal planning models to yield sustainable built environments that attract, enable and empower the complex, characterful and vibrant culture of the Egyptian population.